Edgar Allan Poe (1809-1849) e os contos mesméricos - Agibert, Cibele Pereira (2017)
This thesis deals with an analysis of tales “The Facts in the Case of M. Valdemar” (1845), “Mesmeric Revelation,” (1844) and “A Tale of the Ragged Mountains” (1844) written by Edgar Allan Poe ( 1809-1849), mainly some related to the mesmerism between 18th and 19th centuries. This thesis contains of an introduction and three chapters. Chapter 1 presents Franz Anton Mesmer (1734-1815) and a therapeutic procedures on mesmerism as well as passes, magnets, wands, baquet, magnetized water, and magnetization of animals, trees, objects are used for treatment of diseases. As well as, the followers of Mesmer, as, A.M.J.C.Puységur (1751-1825), J.P.F.Deleuze (1755-1835), Du Potet (1796-1881). Chapter 2 is based on mesmerism, and trance, induced somnambulism, as methods and experiments adopted by magnetists Charles Poyen (?-1844), John Elliotson (1791-1868), James Esdaile (1808-1859), Robert H. Collyer (1814-1891) that used these resources for surgical procedures, mesmeric analgesia. Chapter 3 presents the author Edgar Allan Poe through of mesmeric tales, in view of dialogues of characters Valdemar and Vankirk have suffered from tuberculosis, and Bedloe is subject to severe bouts of neuralgia, and submitted to mesmeric sleep, by physicians Dr. Templeton Dr. P., Dr. D. e Dr. F. e M. P, e Mr. Theodore L., to meet these practices. Likewise, there were authors have used this therapeutic as, Dumas, Balzac, Victor Hugo, Thomas de Quincey, Elizabeth Barrett Browning, in the sense, scholars such as, Harriet Martineau, Chauncy Hare Townshend. Therefore, final remarks on the mesmeric tales related to the medicine. These short stories display a focus of scientific subjects, as mesmerism, diseases, somnambulism, and passes